Aktivitas di alun-alun sebagai ruang terbuka publik dengan konsep lapangan, kasus studi: Alun-alun Bandung - Grace Putri Dianty; Yohanes Basuki Dwisusanto (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Activity in Bandung city square as a public open space with open field concept Bandung city square is an icon of Bandung, known by the public as a public open space with a field in the middle. The shape of the square has changed to resemble a city park with the addition of new facilities in it such as seating area, play area, sport area and so on. The changes affect its function as public space and the activities formed in it. The purpose of this study is to identify patterns of activities and their correspondence with the shape of the square as a public space in the city of Bandung. This study is carried out through stages (1) mapping the functional area based on its physical arrangement; (2) identifying activities formed in it and (3) interviewing the users. The result of the study indicates that the types of activities in Bandung city square are more diverse due to the addition of seating area, play area and renewal of the concept of the field. But besides that, the placement of shade trees in each sitting area needs to be considered so that the square is not only active at night, but also during the daytime.